Phenotypic differences in heavy metal accumulation in populations of the brown macroalgae Fucus vesiculosus: A transplantation experiment. (April 2020) - García-Seoane, R.; Aboal, J.R.; Boquete, M.T.; Fernández, J.A.
Graphical abstract: Highlights: Native algae growing in metal polluted sites are not good biomonitors of water quality. Algae may develop adaptative strategies in response to high toxicity by metals. Algae could block bioconcentration of metals to survive in unfavourable conditions. Transplants of Fucus vesiculosus are suitable for biomonitoring water metal pollution. Abstract: The concentrations of Al, As, Cd, Co, Cr, Cu, Fe, Hg, Ni, Pb and Zn in the thalli of Fucus vesiculosus transplanted reciprocally among four sites affected by different degrees of metal pollution (two unpolluted and two industrial environments) were measured with the aim of comparing the capacity of the algae to accumulate these elements under such conditions. At the beginning of the experiment, the concentrations of all elements differed significantly between the individuals from at least one of the unpolluted and one of the polluted sites. After exposure of the algae for 90 days, the concentrations of all of the elements except As, Cd and Cu in individuals transplanted from the unpolluted sites to the most polluted site increased to higher levels than in the algae transplanted within the site of origin. The same behaviour was observed for all elements except As and Cd in the thalli transplanted from one of the unpolluted sites to the second most polluted site. By contrast, the concentrations of the elements in transplants from the polluted sites exposed in the unpolluted sites usually decreased to approximately the same levels as in the autotransplants. These results suggest that the heavy metal uptake capacity may be limited in F. vesiculosus populations exposed to long-term pollution as an adaptive response to toxicity by metals. We therefore recommend the use of algal transplants to study water quality in highly polluted sites, rather than of native algae already growing in the sites, to avoid the possible effects of such adaptation.